Prespektif Orang Kristen Mengenai Kerajaan Seribu Tahun Berdasarkan Wahyu 20 - Reina Nurani S; Abad Jaya Zega (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The Millennium Age (1000 year reign of Christ on the earth( is a subject that not many Endtime authors speak about. But this is a time period that deserves to be addressed. During the Millennial Age, Satan will be bound and out of action until the end of time. The agent that binds Satan is an angel. The duration of this confinement will be a thousand years. The purpose for this confinement is so that he will no longer be able to deceive the nations. However, at the end of that period he Will be losed